Radical transparency and digital democracy : wikileaks and beyond - Heemsbergen, Luke (Emerald Publishing Limited, 2021)
This book tells the story of radical transparency in a datafied world. The analysis, grounded from past examples of novel forms of mediation, unearths radical change over time, from a trickle of paper-based leaks to the modern digital torrent.